Depressive symptoms and glycated hemoglobin A1c: a reciprocal relationship in a prospective cohort study. Issue 5 (1st December 2015) - Schmitz, N.; Deschênes, S.; Burns, R.; Smith, K. J.
Abstract : Background: The aim of this study was to evaluate the dynamic association between depressive symptoms and glycated hemoglobin A1c (HbA1c) levels using data from the English Longitudinal Study of Ageing (ELSA). Method: The sample was comprised of 2886 participants aged ⩾50 years who participated in three clinical assessments over an 8-year period (21% with prediabetes and 7% with diabetes at baseline). Structural equation models were used to address reciprocal associations between depressive symptoms and HbA1c levels and to evaluate the mediating effects of lifestyle-related behaviors and cardiometabolic factors. Results: We found a reciprocal association between depressive symptoms and HbA1c levels: depressive symptoms at one assessment point predicted HbA1c levels at the next assessment point (standardized β = 0.052) which in turn predicted depressive symptoms at the following assessment point (standardized β = 0.051). Mediation analysis suggested that both lifestyle-related behaviors and cardiometabolic factors might mediate the association between depressive symptoms and HbA1c levels: depressive symptoms at baseline predicted lifestyle-related behaviors and cardiometabolic factors at the next assessment, which in turn predicted HbA1c levels 4 years later. A similar association was observed for the other direction: HbA1c levels at baseline predicted lifestyle-related behaviors and cardiometabolic factors at the next assessment, which in turn predicted depressive symptoms 4 years later. Conclusions: Our results suggest a dynamic relationship between depressive symptoms and HbA1c which might be mediated by both lifestyle and cardiometabolic factors. This has important implications for investigating the pathways which could link depressive symptoms and increased risk of diabetes.